Do Government Grants to Private Charities Crowd Out Giving or Fund-raising? - Andreoni, James; Payne, A. Abigail (American Economic Review, 2003)
Economists have long observed that crowding out of government grants to private charities is incomplete. The accepted belief is that givers treat the grants as imperfect substitutes for private giving. We theoretically and empirically investigate a second reason: the strategic response of a charity will be to reduce fund-raising efforts after receiving a grant. Employing panel data from arts and social service organizations, we find that government grants cause significant reductions in fund-raising. This adds a new dimension to the policy discussions—analysts should account for the behavioral responses of the charity, as well as the donors, to government grants.